RESEARCH OF THE EFFECT OF AGING PROCESS ON DISPERSION OF AIR PHASE AND ICE CRYSTALS IN MILK ICE CREAM - A. A. Tvorogova; P. B. Sitnikova; T. V. Shobanova; R. R. Zakirova (Пищевые системы, 2020)
In this research the results of analytical studies are presented, which prove the lack of data on influence of aging process on dispersion of structural elements in ice cream with fat mass fraction of 6% or less, and experimental studies on definition of dispersion of air phase and ice crystals in milk ice cream. It was found that the process of the mix aging doesn’t significantly affect the dispersion of air phase and ice crystals in ice cream with fat mass fraction of 3%. In ice cream with fat mass fraction of 6%, made from a mix, the dispersion of the air phase increased along with the aging process, and the size of almost all air bubbles were less than 50 microns. At the same time the dispersion of ice crystals increased by no more than 10%. The decrease in dispersion of the air phase during the storage period was observed, mostly in ice cream with a fat mass fraction of 6% produced of the cured mix. The research results have the practical importance as they justify the need for the aging process in the production of ice cream with a low mass fraction of fat and determine the necessity of further research in this area.